COMPARISON OF THE LONG-TERM PROPERTIES IN COMPRESSION OF DIFFERENT SIZE FOAMED CONCRETE (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
Foamed concrete has been used as a building material since the early 1920s. In the beginning, it was used as an insulation material with very low density. Since then there have been attempts to make this material more load-bearing and structural. In the present-day foamed concrete is being used in soil reinforcement, manufacturing of building blocks and other sorts of construction materials. [1] The aim of this article is to determine long-term properties and strength of foamed concrete specimens as well as compare the results between two differently sized foamed concrete specimens. The size of creep and shrinkage specimens were Ø46x190 mm and Ø75x180 mm. The creep properties of the specimens were determined by loading them with 20% of the ultimate stress value. [2] The compressive strength, creep and specific creep of specimens were determined as well as specimen size factor to creep deformations.